The contribution of various sectors in west Malaysia to the economic growth: an input-output analysis - Hassan, Mohd Khairul Hisyam; Mohd Noor, Zaleha; Ismail, Normaz Wana; Radam, Alias; Abdul Rashid, Zakariah (Human Resource Management Academic Research Society, 2019)
By using the regional input-output approach, this paper attempts to analyse the contribution of the various sectors in West Malaysia to economic growth as well as the regional development planning. Our linkage effects strongly suggest that there is a strong argument to believe that a further developed West Malaysia with greater facilities and investment for the petroleum products; other manufacturing; and wholesale and retail trade sectors will make it an increasingly sources of growth in the West Malaysia. Moreover, the empirical results also reveal that petroleum products; electronics and non-electronics; motor vehicles and other transport; and other manufacturing; were among the sectors with high multiplier values in West Malaysia compared to other sectors.